Acceptability, macro nutrients cheese crackers substitutied purple sweet potato and tempeh flour - windasari windasari; Fatmawaty Suaib; Sitti Sahariah Rowa (Media Gizi Pangan, 2019)
Antioxidant are substances that can slow down or prevent the oxidation process. This substance can actually slow down or inhibit oxidation of substance that are easilyoxidazed even in low consentration. Antioxidant are also suitably defined as compounds that protect cells from the harmful effeck of reactive oxygen free radicals if thay are associated with disease, thesefree radicals can come from the body’s metabolism and other external factors. How to accept and the content of macro nutrients to cheese crackers with the substritution of purple sweet potato flour and tempe flour. This study aims to determine the acceptability and content of macro nutrients in cheese crackers with the substritution of purple sweet potato flour and tempe flour. This research is an experimental type that is research that aims to find out symptom or influence that arises as a result of cartain treatment, not rendered and not controlled. The result showed that there were significant effects on aspects of color, smell, taste, and texture on cheese crackers with the substritution of purple sweet potato flour and tempe flour. The most preferred formula is F1 with a concentration 25%. The result of the analysis of macro nutrients in cheese crackers with the substritution of purple sweet potato flour and tempe flour are 7,55% protein, 38,99% fats, 18,68% carbohydrates. Consulsions obtained are cheese crackers produced in this study there are there types of concentration, namely 25% concentration, 50% concentration, and 75% concentration,each of which has a different color, smell, taste and texture. Its recommended for researches to be able to analyze other nutrients from cheese crackers with the substritution of purple sweet potato flour and tempe flour.